2020
DOI: 10.1038/s41598-020-73558-3
|View full text |Cite
|
Sign up to set email alerts
|

Survival prediction of patients with sepsis from age, sex, and septic episode number alone

Abstract: Sepsis is a life-threatening condition caused by an exaggerated reaction of the body to an infection, that leads to organ failure or even death. Since sepsis can kill a patient even in just one hour, survival prediction is an urgent priority among the medical community: even if laboratory tests and hospital analyses can provide insightful information about the patient, in fact, they might not come in time to allow medical doctors to recognize an immediate death risk and treat it properly. In this context, mach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 106 publications
0
36
0
Order By: Relevance
“…To recap, four studies applied machine learning to minimal electronic health records to diagnose sepsis or predict survival of patients [10,11,21,22], while six other studies applied them to complete electronic health records for the same goals [12-14, 16, 17, 19]. The study of Burdick and colleagues [15] even reported an observed decreased in the mortality at the hospital where the computational intelligence methods were applied to recognize sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…To recap, four studies applied machine learning to minimal electronic health records to diagnose sepsis or predict survival of patients [10,11,21,22], while six other studies applied them to complete electronic health records for the same goals [12-14, 16, 17, 19]. The study of Burdick and colleagues [15] even reported an observed decreased in the mortality at the hospital where the computational intelligence methods were applied to recognize sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…age and comorbidities) factors which predict mortality in combination with the SOFA score in patients hospitalized for a restricted list of potentially severe infections ( pneumoniae , necrotizing dermohypodermitis, acute pyelonephritis, acute peritonitis, endocarditis, central venous catheter infection, meningitis, and acute osteoarthritis). Recently, other authors have shown the predictive value of age for sepsis-related mortality [ 69 – 71 ], but none demonstrated an equivalence between “modifiable” and “non-modifiable” factors using a scoring-point system of mortality prediction. Thus, it is interesting that in terms of mortality prediction and in this specific population, a lactatemia of ≥2 mmol/L is barely equivalent to an age of ≥40 years or a Charlson's comorbidity score of ≥2 ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…P <0.05 was considered significant. We used Matthews correlation coefficient (MCC) to evaluate the predictive model, with MCC worst value=– and best value=+1 [ 11 ].…”
Section: Methodsmentioning
confidence: 99%